Literatur Review: Peran Kompensasi Sebagai Faktor Penentu Kepuasan dan Kinerja Karyawan - Asdian, Muhammad; Purwasari, Dwi Rezki Dea; Wulandari, Wulandari; Almasita, Almasita; Setiawan, Ricky (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to analyze the role of compensation as a determining factor for employee satisfaction and performance through a literature review approach. The method used is library research, analyzing 10 scientific articles from nationally accredited journals published between 2020–2025. The results indicate that compensation, both financial and non-financial, has a significant effect on employee job satisfaction. Furthermore, compensation also directly improves employee performance, as well as indirectly through job satisfaction as an intervening variable. These findings underscore the importance of fair and competitive compensation not only as an employee entitlement but also as a strategic tool to enhance retention, motivation, and productivity, which in turn supports overall organizational effectiveness